2023
DOI: 10.1136/tc-2022-057905
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns of cigarette and ENDS transitions in the USA: a multistate transition analysis of youth and adults in the PATH Study in 2015–2017 vs 2017–2019

Abstract: IntroductionIt is unknown how recent changes in the tobacco product marketplace have impacted transitions in cigarette and electronic nicotine delivery system (ENDS) use.MethodsA multistate transition model was applied to 24 242 adults and 12 067 youth in waves 2–4 (2015–2017) and 28 061 adults and 12 538 youth in waves 4 and 5 (2017–2019) of the Population Assessment of Tobacco and Health Study. Transition rates for initiation, cessation and product transitions were estimated in multivariable models, accounti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In previous work, we had identified dramatic increases in the persistence of ENDS-only and dual use of cigarettes and ENDS around the time of the marketplace shift to pod mod products, including JUUL. 7 Here, we found that many of the transition rates that significantly changed from 2015–17 to 2017–19 did not significantly change again in 2017–19 to 2019–21 (Figure S1), including the non-current to cigarette-only use, cigarette-only to non-current use, ENDS-only to dual use, and dual to cigarette-only use transitions. We did find three significant changes in transition rates from 2017–19 to 2019–21: a decline in never-established to cigarette-only use, an increase in ENDS-only to non-current use, and an increase in dual to ENDS-only use.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…In previous work, we had identified dramatic increases in the persistence of ENDS-only and dual use of cigarettes and ENDS around the time of the marketplace shift to pod mod products, including JUUL. 7 Here, we found that many of the transition rates that significantly changed from 2015–17 to 2017–19 did not significantly change again in 2017–19 to 2019–21 (Figure S1), including the non-current to cigarette-only use, cigarette-only to non-current use, ENDS-only to dual use, and dual to cigarette-only use transitions. We did find three significant changes in transition rates from 2017–19 to 2019–21: a decline in never-established to cigarette-only use, an increase in ENDS-only to non-current use, and an increase in dual to ENDS-only use.…”
Section: Discussionmentioning
confidence: 78%
“…Although this analysis primarily focuses on the differences between 2017–19 and 2019–21, we include previous results in 2015–17 in the supplementary material for comparison purposes (Figures S1–S3). 7…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations